Comparison of LFC Optimization on Micro-hydro using PID, CES, and SMES based Firefly Algorithm - Kadaryono Kadaryono; Rukslin Rukslin; Machrus Ali; Askan Askan; Asnun Parwanti; Iwan Cahyono (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Micro-hydro gets potential energy from water flow that has a certain height difference. Potential energy is strongly influenced by high water fall. Potential energy through pipes, incoming turbines converted into kinetic energy. The kinetic energy of the turbine coupled with the generator is converted into electrical energy. Some components used for micro-hydro power generation, among others; intake, settling basin, headrace, penstock, turbine, draft tube, generator, and control panel. Water flows through the pipe into the turbine house so it can rotate the turbine blades. Turbine rotation is used to rotate a generator at the micro hydro generator. The most common problem with micro-hydro generating systems is inconsistent generator rotation caused by changes in connected loads. Load changes can cause system frequency fluctuations and may cause damage to electrical equipment. Artificial Intelligence (AI) is used to obtain the right constants to obtain the best optimization. In this study compare the control method, namely; Proportional Integral Derivatives (PID), Capacitive Energy Storage (CES), and Superconducting Magnetic Energy Storage (SMES). This study also compared the method of artificial intelligence between Particle Swarm Optimization (PSO) method has been studied with the method of Firefly Algorithm (FA). Overall this study compares 11 methods, namely methods; uncontrolled, PID-PSO method, PID-FA method, CES-PSO method, CES-FA method, SMES-PSO method, SMES-FA method, PID-CES-PSO method, PID-CES-FA method, PID-SMES - PSO, and PID-SMES-FA method. The results of the simulation showed that from the 11 methods studied, it was found that the PID-CES-FA method has the smallest undershot value, ie -7.774e-03 pu, the smallest overshoot value, which is 4.482e-05 pu, and the fastest completion time is 7.11 s. These results indicate that the smallest frequency fluctuations are found in the PID-CES-FA controller. Thus it is stated that the PID-CES-FA method is the best method used in the previous method. This research will use other methods to get the best controller.